Genetic Algorithm Coupled with FEM-3D for Metrological Optimal Design of Combined Current-Voltage Instrument Transformer - Marija Cundeva, Ljupco Arsov, Goga Cvetkovski (Emerald Publishing Limited, 2004)
he combined current‐voltage instrument transformer (CCVIT) is a complex non‐linear electromagnetic system with increased voltage, current and phase displacement errors. Genetic algorithm (GA) coupled with finite element method (FEM‐3D) is applied for CCVIT optimal design. The optimal design objective function is the metrological parameters minimum. The magnetic field analysis made by FEM‐3D enables exact estimation of the four CCVIT windings leakage reactances. The initial CCVIT design is made according to analytical transformer theory. The FEM‐3D results are a basis for the further GA optimal design. Compares the initial and GA optimal output CCVIT parameters. The GA coupled with FEM‐3D derives metrologically positive design results, which leads to higher CCVIT accuracy class.
Keywords: Genetic algorithms, transformers, finite elemen method